Bayangan Sebagai Inspirasi pada Penciptaan Karya Seni Grafis Cetak Tinggi - Aryani, Ni Nyoman Ayu Suti; Wirakesuma, I Nengah; Setem, I Wayan (Program Studi Seni Murni ISI Bali, 2025)
Shadows can be used as an interesting element in the creation of high-print graphic art. In the concept carried out in this final report, shadows are not only a visual representation but also a source of inspiration for the author. In the process of creating this artwork, the high print technique is used as the main technique, and a combination of several other media. Humans usually copy the surrounding nature as their aesthetic, which they usually find as experiences and memories. This form of experience is referred to as aesthetic experience or can also be referred to as inspiration. According to Munro, aesthetic experience is the way a stimulus responds to something that exists from outside the self, not just through sensory perception, but also related to psychological processes such as imagination and emotion Based on this description, shadows can be an object of aesthetic experience for the subject as a spectator and creator in the creation of a work. The shape of the shadow, which changes every time, gives room for exploration and understanding of the shapes produced by shadows, especially shadows from plants. Shadows from plants become the main object because they can be found every day. They become a form of experience that is familiar, aesthetic, and interesting to be used as a source of inspiration for creating high-print graphic art.